Microsoft application virtualization advanced guide : master Microsoft App-V by taking a deep dive into advanced topics and acquire all the necessary skills to optimize your application virtualization platform /: master Microsoft App-V by taking a deep dive into advanced topics and acquire all the necessary skills to optimize your application virtualization platform. (©2012) - Unknown
No abstract available